1975
DOI: 10.1084/jem.142.6.1534
|View full text |Cite
|
Sign up to set email alerts
|

Growth of B-lymphocyte colonies in vitro.

Abstract: In semisolid agar cultures containing mercaptoethanol, cells from the spleen, lymph nodes, marrow, peritoneal cavity, thoracic duct, and blood of normal mice generated clusters and colonies of up to 3,000 cells. Colony numbers and growth were markedly enhanced by the addition of sheep red cells. The frequency of colony-forming cells in the spleen or lymph nodes was 0.5-2.0%, and cluster forming cells were approximately five times more numerous. The mononuclear cells comprising these colonies had the electronmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
1
1

Year Published

1976
1976
1991
1991

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 151 publications
(40 citation statements)
references
References 12 publications
1
37
1
1
Order By: Relevance
“…Colony formation is mitogen dependent (17) and the addition of the B-cell mitogen LPS, or SRBC enhances colony formation, particularly when few B cells are cultured (20). We therefore compared the dose response of lymph node cells cultured with or without these agents.…”
Section: Comparison Of Macrophage-containing Underlayers With Other Pmentioning
confidence: 99%
“…Colony formation is mitogen dependent (17) and the addition of the B-cell mitogen LPS, or SRBC enhances colony formation, particularly when few B cells are cultured (20). We therefore compared the dose response of lymph node cells cultured with or without these agents.…”
Section: Comparison Of Macrophage-containing Underlayers With Other Pmentioning
confidence: 99%
“…Thus, in 10 experiments in which control cultures contained 0X1 ml normal saline, the mean number of colonies developing was 10 + 5. In cultures containing 0a1 ml of 10% fresh sheep red cells, colony formation is potentiated and becomes linear with respect to the number of cells cultured (Metcalf et al, 1975b). Thus, in the above experiments, a mean of 207 ± 93 colonies was observed in cultures containing 0-1 ml of 10% sheep red cells.…”
Section: General Effects Of Human Serummentioning
confidence: 72%
“…Because of the deliberate use of low numbers of cultured cells to obtain suboptimal culture conditions (Metcalf et al, 1975b) some fluctuation occurred between different experiments in the level of Blymphocyte colony formation obtained in the control cultures. Preliminary studies in 10 control experiments showed that cultures of 25,000 C57BL spleen cells usually produced 10 ± 5 colonies with the addition of 041 ml of normal saline, 150-250 colonies with the addition of 041 ml of 10% sheep red cells, and 10-20 colonies with 041 ml of the 3 control human sera (usually at a dilution between 1 : 4 and 1 : 16).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations